Adiponectin, in contrast to leptin, is not associated with body mass index, waist circumference and HOMA-IR in subjects of a west-African population - Awede, Bonaventure; ADOVOEKPE, Diane; ADEHAN, Grace; MacFarlane, Niall; AZONBAKIN, AZANDÉGBÉ SIMON; DOSSOU, Emmanuel; AMOUSSOU GUENOU, Marcellin; DJROLLO, Francois (My University, 2018)
Factors associated with plasma levels of adiponectin and leptin were studied in adult subjects without diabetes from Cotonou in Benin (West-Africa). Seventy (70) men and 45 women were included in the study. Anthropometric variables were measured and a venous blood sample was drawn from each subject, after an overnight fasting period, for measurement of plasma glucose, insulin, leptin, and adiponectin levels. HOMA-IR was determined to assess insulin resistance. Adiponectin and leptin levels were higher in women than in men (with adiponectin 18.48 12.77 vs.7.8 10.39 lg/mL, P < 0.0001, and leptin 30.77 19.16 vs. 8.66 8.24 ng/mL, P < 0.0001). Fasting insulin level and HOMA-IR were also higher in the females. Hyperleptinemia was observed in 66,96% of subjects and hypoadiponectinemia was present in 44.35% of subjects. In both men and women, leptin correlated with age (r = 0.2; P = 0.02), BMI (r = 0.572; P < 0.0001), waist circumference (r = 0.534; P < 0.0001), fasting insulin (r = 0.461; P < 0.001), and HOMA-IR (r = 0.430; P < 0.0001). No significant correlation was observed for adiponectin levels with these variables. Only in women, adiponectin was inversely correlated with fasting glucose (r = 0.423; P < 0.004). These data confirm previous descriptions of leptin but suggest that variations in factors determining serum adiponectin levels observed between ethnicities could also been seen between populations from the same ethnicity.
Keywords: Keywords; Adiponectin; insulin resistance; leptin; obesity.